Evaluation of Effects of Specific Bioactive Compounds in Plant, Propolis and Bee-Pollen on Crohn’s Disease: A Food Nutrition Approach - Leila Mehdizadehtapeh; Nesli Nur Mercan; Ceren Demir; Mehmet Özbil; Hüseyin Abdik; Sinem Nur Açıkgöz; Serap Andaç; Ahmad Nimatullah Al-Baarri; İsmail Hakkı Tekiner (Diponegoro University, 2025)
Natural foods rich in bioactive compounds (BC) may provide an effective strategy for food and nutrition-based Crohn's disease (CD) management. However, their BCs’ alone and combined effects have not been explored sufficiently. This study aims to evaluate the impact of specific BCs in plants, propolis, and bee pollen on CD by in silico and in vitro techniques. For this, the plants suggested in a clinical database were screened in another curated therapeutic database to obtain specific BCs with therapeutic use identifiers. In contrast, those of propolis and bee pollen were obtained from previously conducted publications. The identified BCs were subjected to in silico molecular docking simulations (MDS) to determine their binding affinity scores (BAS) with aryl hydrocarbon receptor (Ahr). Of them, two with the highest affinity score (AS) and the other two with the lowest AS were selected. Their cytotoxic effects on HCT-116 Human colon cancer cells were tested by in vitro MTS assay, while up- and downregulating effects on Ahr-related CYP1A1, CYP1B1, IDO1, and IDO2 genes by real-time qPCR. The findings demonstrated that MDS studies determined the highest BAS with Ahr to be β-carotene (β-C) (-8.99 kcal/mol) and biotin (B) (-6.39 kcal/mol). In comparison, the lowest BAS was to inositol (I) (-5.34 kcal/mol) and niacin (N) (-5.32 kcal/mol), respectively. In vitro MTS assay demonstrated that N and I were cytotoxic on HCT-116 cells, while β-C was noncytotoxic. But B did not exhibit any significant effect. The gene expression test showed that β-C downregulated IDO1 and IDO2, while B downregulated IDO1 only. On the other hand, N downregulated both CYP1A1 and IDO2, whereas I downregulated CYP1A1 only. β-C and B in combination upregulated all genes, but N and I downregulated them. In conclusion, proper selection of BC may effectively moderate CD pathogenesis and management with its protective and anti-inflammatory properties. We therefore suggest food and nutrition-associated research at preclinical and clinical levels.